Economics of Cardamom Cultivation in Kerala - P.K. Varghese (Ind. Jn. of Agri. Econ., 2007)
The three important concepts - costs, return and profitability need to be analysed while assessing the economics of any production activity. Among these, the most controversial one is the computation of cost of cultivation, especially for perennial crops, which have long gestation periods. Estimation of imputed costs like family labour further adds to the problem of calculating the cost of cultivation of agricultural produce. An attempt has been made here to estimate the cost of production of cardamom in Kerala. Also an attempt is made to work out the relative profitability of cardamom using cost-benefit analysis, net present value and internal rate of return. The analysis of the cost and return from the cultivation and the production of cardamom will provide a synoptic view of the economics of production of this spice crop in Kerala